Sistem Pemantauan Lingkungan Kandang Ayam Dan Otomatisasi Pemberian Pakan Menggunakan Metode Fuzzy Logic Type-2 Dan Aplikasi IOT (Internet Of Things) - Ahmadi; Priantono, Didik (Fakultas Teknik Universitas Bhayangkara Surabaya, 2025)
High mortality rates in broiler chicks using conventional chicken coops can cause losses for chicken farmers. From this study, a solution to the problem was obtained, namely by creating a chicken coop environmental monitoring system and also automation in providing feed and drink efficiently. Applying the DHT22 sensor as a temperature and humidity detector and the MQ135 sensor as a detector of ammonia gas levels in the coop with the application of the fuzzy logic type-2 algorithm as a control system for monitoring the chicken coop. Using scheduled feed automation according to the age of the chicks until they become adults, using a water level sensor as a detector of drinking water in the coop automatically. Making two comparisons of conventional coops with smart coops and getting test results with quite good differences where if using a conventional coop with only using incandescent lamp heating, the chicks can only survive at the age of 9 days and die every day after that in other chicks. By using a comparison of 8 chicks in each coop. The weight of conventional cage chicks that were initially 5 days old weighed 39.4 grams to 42.9 grams, while in smart cages with 8 chicks and only 3 chicken deaths with an initial weight of 40.1 grams to 258.1 grams and early death occurred at the age of 13 days, can survive a little longer than chickens with conventional cages. From these results, it was found that smart chicken cages were superior to conventional cages without a cage environmental monitoring system and a success rate of 62.5% of 8 chicks with 3 chickens that died.